Alfred Bester’s The Stars My Destination - Wilson, D. Harlan. author. aut Link
XI, 124 p. 1 illus.
Keywords: In this comprehensive study of The Stars My Destination, D. Harlan Wilson makes a case for the continued significance of Alfred Bester’s SF masterwork, exploring its distinctive style, influences, intertextuality, affect, and innovation as well as its extensive metafictional properties. In Stars, Bester established himself as a son of the pulp-SF and high-modernist writers that preceded him and a forefather to the New Wave and cyberpunk movements that followed his lead. Wilson’s study depicts Bester as an SF insider as much as an outlier, writing in the spirit of the genre but breaking with the fixation on hard science in favor of psychological interiority, literary experimentation, and adult themes. The book combines close-readings of the novel with broader concerns about contemporary media, technoculture, and the current state of SF itself. In Wilson’s view, SF is a moribund artform, and Stars foresaw the inevitable science fictionalizationof our benighted world. With scholarly lucidity and precision, Wilson shows us that Stars pointed the way to what we have (un)become. D. Harlan Wilson is an American novelist, playwright, editor, critic, and Professor of English at the Lake Campus of Wright State University, USA. He is the author of over 30 book-length works of fiction and nonfiction.